(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
In this work, the a-posteriori error indicator with an explicit formula for p-version finite element methods in square is investigated, and its reliable and efficient properties are deduced. Especially, this a-posteriori error indicator is determined by the right hand item of the model. We reformulate this a-posteriori error indicator with finite coefficients, which can be easily calculated during applications.